FPGA configuration of an alloyed correlated branch predictor used with RISC processor for educational purposes - Mahmood, Hadeel SH. (International Journal of Electrical and Computer Engineering (IJECE), 2021)
Instructions pipelining is one of the most outstanding techniques used in improving processor speed; nonetheless, these pipelined stages are constantly facing stalls that caused by nested conditional branches. During the execution of nested conditional branches, the behavior of the running branch depends on the history information of the previous ones; therefore, these branches have the greatest effect in reducing the prediction accuracy of a branch predictor among conditional branches. The purpose of this research is to reduce the stall cycles caused by correlated branches misprediction by introducing a hardware model of a branch predictor that combines both local and global prediction techniques. This predictor integrates the prediction characteristics of the alloyed predictor with those of the correlated predictor. the predictor design which implemented in VHDL (Very high-speed IC hardware description language) was inserted in previously designed MIPS (microprocessor without interlocked pipelined stages) processor and its prediction accuracy was confirmed by executing a program using the selection sort algorithm to sort 100 input numbers of different combinations ascendingly.